2015
DOI: 10.2527/jas.2014-8539
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three patterns of feed supplementation with live Saccharomyces cerevisiae yeast on postweaning diarrhea, health status, and blood metabolic profile of susceptible weaning pigs orally challenged with Escherichia coli F4ac1

Abstract: The development of effective feeding strategies to reduce the detrimental effect of enterotoxigenic F4ac (ETEC) plays a crucial role in reducing the occurrence of therapeutic intervention with antibiotics in livestock. The ability of CNCM I-4407 (SCC), supplied in different patterns to counteract ETEC infection in weaned pigs, was evaluated. Fifty pigs weaned at 24 d were then divided into 5 groups: control (CO), CO + colistin (AB), CO + 5 × 10(10) cfu of SCC/ kg feed, from d 0 to 21 (PR), CO + 5 × 10(10) cfu … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 36 publications
3
36
0
Order By: Relevance
“…In our study, ETEC adhered to the intestinal villi of all pigs and presumably started to activate the cell signaling involved in cell turnover and inflammation (Zhou et al, 2012). In the follow-up experiment (Trevisi et al, 2015a), the fecal score evidenced the first signs of diarrhea from 24 h after infection. Thus, the infection may have reduced the mitotic potential in the villi while the protective effects of the antibiotic preserved the normal proliferative activity of the intestinal mucosa as observed in pigs preventively treated with yeast.…”
Section: Discussionmentioning
confidence: 50%
See 4 more Smart Citations
“…In our study, ETEC adhered to the intestinal villi of all pigs and presumably started to activate the cell signaling involved in cell turnover and inflammation (Zhou et al, 2012). In the follow-up experiment (Trevisi et al, 2015a), the fecal score evidenced the first signs of diarrhea from 24 h after infection. Thus, the infection may have reduced the mitotic potential in the villi while the protective effects of the antibiotic preserved the normal proliferative activity of the intestinal mucosa as observed in pigs preventively treated with yeast.…”
Section: Discussionmentioning
confidence: 50%
“…Our previous companion paper reported that the preventive supplementation of Sc reduced the diarrhea occurrence in the first days after infection with ETEC and delayed mortality (Trevisi et al, 2015a); the results were similar even when the supplementation started immediately before the ETEC challenge.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations